Genotype x environment interaction in Arachis pintoi - International Center for Tropical Agriculture (2016)
Agronomic evaluation. In 1994, the available 27 accessions of Arachis pintoi and 5 of Arachis repens, were planted at 6 sites in Colombia to evaluate genotype-environment interaction. The environments ranged from the humid tropics (Macagual and La Rueda in Caqueta), the savannas (a sandy loam (Alegria) and clay loam (Alcancla) soil sites at Carimagua, Meta) to the seasonally dry hillsides (a fertile clay loam at Chinchina and a silty loam at Popayan). The legume was established in association with a common grass (Brachiaria humidicola CIAT 6133, formerly Brachiaria dictyoneura). After an initial harvest and standardization cut, management has been by heavy grazing at monthly intervals.